PIVOTING COVID-19 VACCINATION THROUGH MVAX: A PERSPECTIVE FROM AN LMIC SETUP - Allana, Raheel; Allana, Asad (Journal of Ayub Medical College Abbottabad, 2022)
Several countries including Pakistan have already started deploying booster vaccinations owing to the COVID-19 pandemic yet in Pakistan populace is not fully vaccinated yet and currently Pakistan has bracied for another potential Covid-19 surge, as the number of cases in the nation has been escalating, driving the positive rate even higher. Vaccine inequity and acceptance has been an issue in Pakistan owing to lack of knowledge, lack of proximity to healthcare facilities, poor socio-economic status, etc. Also, the behaviour of the populace in Pakistan varies from that of other countries in that when COVID-19 cases declined, individuals thought the virus has been abolished and they stopped following standard operating procedures (SOPs). In this context, this article introduces the notion of mobile vaccination for everyone, which may be implemented to improve vaccination coverage.